Perancangan Sistem Informasi Wisata Religi Berbasis Website di Bali - I Gede Agus Krisna Warmayana (UHN IGB Sugriwa Denpasar, 2018)
Bali is a tourist destination famous for its thousand temples and customary customs that are interrelated so closely. The information system is a combination of information technology and the activities of people using technology to support operations and management. Religious Tourist (tirtayatra) information system is an information system built to meet the information needs of the holy places in Bali in doing yajna supported facilities such as hotels, transportation and eating places. This design emphasizes on the process of making religious tourism (tirtayatra) information system into a useful information system for tourists to facilitate and quickly search for holy places. The design of religious tourism (tirtayatra) information system can provide information such as holy places, hotels, restaurants, news, and articles. This system is implemented in Bali, by providing tools for searching and information about tourism facilities along with photos for relegi tours. System design method used to identify components of information system design includes elements of website creation, DFD Design, ERD and database table structure. For making this informationsystem using Macromedia Dreamweaver software with PHP programming language and MySQL database. The problem in this journal is how to design and build a web-based tourism information system. The purpose of this journal is to analyze, design and build aweb-based tourism information system that can provide information to users related to the objects of sacred places and their supporting facilities.